2021
DOI: 10.1111/andr.13052
|View full text |Cite
|
Sign up to set email alerts
|

Health and health care access in the US transgender population health (TransPop) survey

Abstract: Background: Probability and nonprobability-based studies of US transgender persons identify different disparities in health and health care access. Objectives:We used TransPop, the first US national probability survey of transgender persons, to describe and compare measures of health and health access among transgender, nonbinary, and cisgender participants. We directly compared the results with 2015 US Transgender Survey (USTS) data and with previously published analyses from the Behavioral Risk Factor Survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…For instance, a national probability survey of transgender people reported a higher percentage of young people identifying as nonbinary (including genderfluid and genderqueer) and those of older age groups were more likely to use binary transgender identities (trans man and trans woman). 19 Therefore, a narrow conceptualization of sexuality and gender, especially from a cisheterosexist perspective, is likely to lose its applicability over the years. It is not uncommon to come across victim-blaming narratives around LGBTQ people in Malaysia.…”
Section: Lgbtq People Have Poor Mental Health?mentioning
confidence: 99%
“…For instance, a national probability survey of transgender people reported a higher percentage of young people identifying as nonbinary (including genderfluid and genderqueer) and those of older age groups were more likely to use binary transgender identities (trans man and trans woman). 19 Therefore, a narrow conceptualization of sexuality and gender, especially from a cisheterosexist perspective, is likely to lose its applicability over the years. It is not uncommon to come across victim-blaming narratives around LGBTQ people in Malaysia.…”
Section: Lgbtq People Have Poor Mental Health?mentioning
confidence: 99%
“…From a medical standpoint, Feldman et al describe and compare measures of health and health access among TGD and cisgender adults from the first national probability survey of its kind in the United States called TransPop. 8 They found that despite equally high insurance coverage, TGD people more often avoided care due to cost. As compared to cisgender respondents, TGD respondents were more likely to rate their health as fair/poor and have more poor physical and mental health days.…”
Section: E D I T O R I a L The Growing And Interdisciplinary Field Of...mentioning
confidence: 99%
“…From a medical standpoint, Feldman et al. describe and compare measures of health and health access among TGD and cisgender adults from the first national probability survey of its kind in the United States called TransPop 8 . They found that despite equally high insurance coverage, TGD people more often avoided care due to cost.…”
mentioning
confidence: 99%
“…A growing body of literature has started to document the growing health disparities and inequities impacting transgender women of color (TWC) ( 1 – 5 ). TWC encounter structural barriers related to having appropriate access to health care, limited opportunities to a formal employment, structural violence, victimization, discrimination, migration, and housing instability ( 6 – 10 ). In particular, migration is a public health concern affecting TWC in the U.S.-Mexico border region.…”
Section: Introductionmentioning
confidence: 99%